SYSTEMIC ETIOLOGY OF GINGIVAL OVERGROWTH: CLINICAL AND THERAPEUTIC ASPECTS. LITERATURE REVIEW - Anca Mihaela Predescu; Dan Alexandru Popescu; Gabriela Boldeanu; Cristina Maria Munteanu; Anda-Elena Crișan; Elena Cristina Andrei; Ilona Mihaela Liliac; Ciprian Laurențiu Pătru (Romanian Dental Association for Education, 2024)
Introduction Drug-induced gingival overgrowth is a condition characterized by a series of modifications in the gingival mucosa, including tumefaction, changes in color, and gingival bleeding. This condition can involve a variety of drugs, such as anticonvulsants and calcium channel blockers. Aim of the study To present the clinical modifications of hypertrophic gingival overgrowth of systemic and drug etiology, as well as to highlight therapeutic alternatives. Results Key aspects of drug-induced gingival overgrowth include the risk of recurrence, the importance of eliminating predisposing factors such as poor oral hygiene and bacterial plaque, as well as treatment options, such as surgical excision, which can be performed with diode dental laser or traditional techniques. Conclusions A personalized therapeutic approach, considering clinical and morphological aspects, is essential for achieving an optimal outcome in managing this condition.